Performance and Emission Characteristics of C.I Engine Equipped with EGR and Chicken Waste Based Biodiesel Blended as a fuel (International Journal of Food and Nutritional Sciences, 2022)
As the world's fossil fuel stocks continue to dwindle at an alarming rate, people are exploring alternatives using oils derived from plants and animals. While most vegetable oils are safe for human consumption, there has been rising interest in experimenting with non-edible and waste fats as a replacement for petro diesel. As in the process of bringing forth clean and green energies into economical usage, manufacturing of Bio-diesel from chicken waste, which is a waste product all over the world generating, disposal problem, has tried. Main purpose of the present study is to analyse the performance and emissions characteristics of biodiesel obtained from chicken waste oil in an unmodified diesel engine and to compare the results with baseline values of diesel fuel. Experimental evaluations of key physicochemical features of transesterified chicken waste oil were determined to be within acceptable limits of applicable standards.In this study, we compare the braking thermal efficiency of biodiesel made from chicken waste at 20%, 40%, and 60% concentrations with that of mineral Diesel, among other performance indicators. Diesel fuel, which has fewer oxygen atoms than biodiesel fuels, produces more carbon monoxide. The increased oxygen content in biodiesel fuel molecules and the lower cetane number (CN) of biodiesel fuels cause biodiesel fuels to produce more NOX than diesel fuel. The drop in flame temperature and the increase in O2 in the fresh air charge cause CO to rise and NOX to fall as EGR is increased. The BTE of diesel was 1.7%-18% lower when blended with biodiesel made from chicken manure. Carbon monoxide, carbon dioxide, unburned hydrocarbon (UBHC), oxides of nitrogen, and smoke opacity were all measured as emission parameters for various test fuels. Chicken waste biodiesel fuel had lower levels of UBHC, CO, CO2, and smoke. When compared to Diesel, however, both pure chicken waste biodiesel and its combination produced more nitrogen oxide emissions.